Applicability of Relationship Intentions among the Civil and Building Engineering Contractors in the South African Construction Sector: A Case of B2B Industry - Xitshembhiso Difference Chauke; Lehlohonolo Amos Masitenyane; Bakae Aubrey Mokoena (African Journal of Inter-Multidisciplinary Studies, 2025)
It is commonly believed that it is more expensive to attract new business than to invest in existing customers. This study investigates the applicability of relationship intention among civil and building engineering contractors (CBEC) and their concrete product suppliers (CPS). Furthermore, ascertains whether the duration of business support stimulates CBEC’s intention to engage in business-to-business (B2B) relational exchanges. Very few studies attempted to explore if there is a statistically significant relationship between CBEC relationship intention and CPS in relation to the duration or length of support towards CPS. A cross-sectional descriptive research design was followed, using a probability simple random sampling procedure to collect data from CBEC operating in Gauteng, South Africa. Using structured self-administered questionnaires, data analysis embraced descriptive statistics, Exploratory Factor Analysis, Independent sample t-test and ANOVA. The findings suggest that it is possible to classify customers based on their relationship intention echelons with differing relationship ideas and dissimilar behaviour across the eight dimensions of relationship intention. For marketers operating within concrete product markets, a strategic recommendation emerges that relationship marketing efforts should be channeled towards customers who exhibit pronounced relationship intentions rather than directing their resources solely on the duration of business association. By diligently considering eight dimensions encompassing relationship intention, CPS can enhance their prospects of cultivating customer relationships that could ultimately lead to improved sales performance and improved profits through mutual benefits and continued relational intentions aimed at intensifying customer retention levels.